A contextual behavioral model of chemsex: structural equation modeling of psychological predictors of hypersexuality and drug use - Rico, Rubén; Montesinos, Francisco (Frontiers in Psychology, 2025)
Background and objectiveChemsex, defined as the intentional use of psychoactive substances in sexual contexts, is increasingly prevalent among gay and bisexual men and is associated with a range of mental, physical and social implications. This study aimed to test a contextual behavioral model examining how psychological inflexibility, loneliness, intimacy difficulties, and internalized homophobia contribute to hypersexuality and sexualized substance use.MethodsA cross-sectional study was conducted with 252 Spanish-speaking participants who reported engaging in sexualized substance use within the past year. Standardized self-report measures were used to assess psychological processes and behavioral outcomes. Structural equation modeling was employed to examine direct and indirect effects among variables.ResultsThe proposed path model demonstrated excellent fit (χ2 = 0.002, p = 0.967; CFI = 1.000; RMSEA = 0.000). Psychological inflexibility showed the strongest association with both hypersexuality (β = 0.48, p < 0.001) and substance use (β = 0.25, p < 0.01), with a significant indirect effect via hypersexuality. Loneliness was also associated with both outcomes and showed mediated effects. Internalized homophobia was associated with hypersexuality but not with substance use. Intimacy was not a significant predictor. The model explained 42.1% of the variance in hypersexuality and 27.2% in substance use.ConclusionThis study offers a novel contribution by modeling chemsex-related behaviors as forms of experiential avoidance shaped by psychological inflexibility, loneliness, and internalized homophobia. The findings highlight the potential utility of Acceptance and Commitment Therapy (ACT) in reducing chemsex vulnerability by promoting psychological flexibility and values-based living.